PENGARUH AIR KELAPA MUDA TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI: TINJAUAN NARATIF - Abdullah, Dessy; Syifa Maharani (Yayasan Nusantara Hasana Berdikari, 2025)
Hypertension is a major risk factor for global cardiovascular disease, and non-pharmacological interventions are increasingly considered in its management. Young coconut water (Cocos nucifera)—a natural beverage rich in potassium and other minerals—is often used by the public as an alternative therapy due to its affordability and safety. This narrative review aims to evaluate the latest literature evidence (2019–2024) on the effect of regular consumption of young coconut water on lowering blood pressure in hypertensive patients. A literature search was conducted in PubMed and Google Scholar databases using the keywords “hypertension” and “young coconut water” (including publications published between 2019–2024). The selected articles were reviewed qualitatively. Several experimental/quasi-experimental studies reported significant reductions in systolic (SBP) and/or diastolic (DDBP) blood pressure after consuming 150–300 ml of young coconut water per day for 1–6 weeks. The mean BP decreased from 145.8 to 135.3 mmHg (p=0.0002) and DBP from 93.7 to 86.9 mmHg (p<0.00001) in the intervention group compared to the control group. The mechanism of this decrease is associated with the high potassium content and diuretic effect of young coconut water, which increases sodium excretion and suppresses the renin–angiotensin–aldosterone system (RAAS). Regular consumption of young coconut water is effective in helping lower blood pressure in hypertensive patients, with the advantages of low cost and a good safety profile. These findings support the potential of young coconut water as a non-pharmacological adjunct therapy in the management of hypertension.